Bone and bone derived factors in kidney disease - Simic, Petra (Frontiers in Physiology, 2024)
Purpose of review: Mineral and bone disorder (MBD) is a prevalent complication in chronic kidney disease (CKD), significantly impacting overall health with multifaceted implications including fractures, cardiovascular events, and mortality. Despite its pervasive nature, effective treatments for CKD-MBD are lacking, emphasizing the urgency to advance understanding and therapeutic interventions. Bone metabolism intricacies, influenced by factors like 1,25 dihydroxy vitamin D, parathyroid hormone (PTH), and fibroblast growth factor 23 (FGF23), along with intrinsic osseous mechanisms, play pivotal roles in CKD. Skeletal abnormalities precede hormonal changes, persisting even with normalized systemic mineral parameters, necessitating a comprehensive approach to address both aspects.In this review, we explore novel pathways involved in the regulation of systemic mineral bone disease factors, specifically examining anemia, inflammation, and metabolic pathways. Special emphasis is placed on internal bone mechanisms, such as hepatocyte nuclear factor 4α, transforming growth factor-β1, and sclerostin, which play crucial roles in the progression of renal osteodystrophy.